Design of Novel Carboxamides of Eremomycin and Vancomycin with 4- or 3-Amino Methyl Phenyl Boric Acid and Their Investigation - E. N. Bychkova; A. M. Korolev; E. N. Olsufyeva; E. P. Mirchink; E. B. Isakova (Антибиотики и Химиотерапия, 2020)
Amidation of the end carboxyl group of eremomycin and vancomycin by pinacolinic 4- or 3-amino methyl phenyl boron acids esters in the presence of the condensing reagent PyBOP resulted in formation of novel carboxamides of the antibiotics (IIIa-VIa). After elimination of the pinacolinic group under mild hydrolysis in weak acid aqueous medium there formed the respective derivatives with a residue of the nonprotected boric acid (III-VI). It was shown that the activity of the 4-substituted derivatives of the borole-containing eremomycin and vancomycin practically was the same as that of the initial antibiotics, while higher than that of the respective 3-substituted derivatives of the borole-containing derivatives against 8 strains of grampositive bacteria.